An examination of the relations between emotion dysregulation, dissociation, and self-injury among dissociative disorder patients. Issue 1 (31st December 2022) - Nester, M. Shae; Brand, Bethany L.; Schielke, Hugo J.; Kumar, Shaina
ABSTRACT: Background: Dissociative disorder (DD) patients report high rates of self-injury. Previous studies have found dissociation and self-injury to be related to emotional distress. To the best of our knowledge, however, the link between emotion dysregulation and self-injury has not yet been examined within a DD population. Objective: The present study investigated relations between emotion dysregulation, dissociation, and self-injury in DD patients, and explored patterns of emotion dysregulation difficulties among DD patients with and without recent histories of self-injury. Method: We utilized linear and logistic regressions and t -test statistical methods to examine data from 235 patient-clinician dyads enrolled in the TOP DD Network Study. Results: Analyses revealed emotion dysregulation was associated with heightened dissociative symptoms and greater endorsement of self-injury in the past six months. Further, patients with a history of self-injury in the past six months reported more severe emotion dysregulation and dissociation than those without recent self-injury. As a group, DD patients reported the greatest difficulty engaging in goal-directed activities when distressed, followed by lack of emotional awareness and nonacceptance of emotional experiences. DD patients demonstrated similar patterns of emotion dysregulation difficulties irrespective of recent self-injury status. Conclusions: Results support recommendations to strengthen emotion regulation skills as a means to decrease symptoms of dissociation and self-injury in DD patients. HIGHLIGHTS: The current study found that emotional dysregulation in DD patients was associated with heightened dissociative symptoms and greater endorsement of self-injury in the past six months.